Economic Value of Management Feedlot Waste and Use as Input Production for Maize Farming System in the Dryland Farming – East Nusa Tenggara – Indonesia - Yohanes Leki Seran; Frans Umbu Datta; Maria Y. Luruk; Ulrikus Romsen Lole; Yoseph Seran Mau; Twentofel O. Dami Dato; Maria Krova (Ravine Publisher, 2024)
In regions where fertilizer subsidies for crucial elements like nitrogen, phosphorus, and potassium are severely limited for farmers, accessing necessary inputs for maize farming becomes a significant challenge. To address this, leveraging local resources such as feedlot waste emerges as a promising solution. This research uses a Random block design to implement this research within three replications. This research uses factorial treatments that are: 1) Without compost and biochar (control), 2) 10 ton/ha compost and biochar, 3) 10 ton/ha compost and biochar and one time application/week, 4) 10 ton/ha compost and biochar one time application/2 week. Replication of all the treatments in this research is three replications. This research aims to assess the economic value of feedlot waste, particularly in its conversion to compost, biochar, and biourine, serving as locally generated inputs for maize production in dryland farming systems. The objectives of this research are to know the economic value of feedlot waste that farmers save and to know the capability of input production from feedlot waste to produce maize in managing dryland farming systems. The result of this research is farmers can save their money for buying input production by managing the waste of feedlots to compost, biochar, and biourine and use it as quality input production.